Radiocarpal Osteochondral Allografts for Wrist Pain Postproximal Row Carpectomy - Bagdady, Kazimir R.; Slovacek, Cedar; Firouzbakht, Peter K.; Mailey, Brian A. (Journal of Wrist Surgery, 2024)
Background Surgical options for patients with recurrent wrist pain after salvage procedures, such as proximal row carpectomy (PRC), are limited and primarily result in total wrist arthrodesis (TWA). Osteochondral allografting (OCA) offers an additional option to address refractory wrist pain due to arthritis while preserving some range of motion.Case Description A 65-year-old, right hand dominant male developed chronic wrist pain, secondary to untreated scapholunate and triangular fibrocartilage complex ligament tears. The patient underwent a PRC, radial styloidectomy, and partial wrist denervation with good initial pain relief. Two years later, symptoms returned with radiographs demonstrating capitate sclerosis. A salvage arthroplasty with OCA produced relief of symptoms.Literature Review Refractory wrist pain after salvage procedures have traditionally been managed with TWA or less commonly, wrist arthroplasty. Capitate resurfacing and interposition have expanded indications for PRC. OCA is a chondral replacement procedure that utilizes cadaveric cartilage allograft plugs to replace damaged cartilage in various articular joint surfaces. Although OCA used in the lower extremity and shoulder has demonstrated improved pain relief and return of function, it has not been reported in the wrist.Clinical Relevance There are limited options for refractory wrist pain after salvage procedures. We present an additional alternative to TWA, by resurfacing the radiocarpal joint affected by chondromalacia after a PRC. This option offers another treatment modality for recurrent wrist pain while still preserving some element of range of motion.
Keywords: osteochondral allograft; radiocarpal arthritis; wrist pain; proximal row carpectomy